PENGARUH PROFITABILITASDAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Edi Purnomo (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study was to describe the effect of profitability, leverage on value of the company with capital structure as intervening variable. This study classified as a quantitative research. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in periode 2012 to 2016. Sample was determined by purposive sampling, there are 15 manufacturing companies. The data is secondary. Data was collected by IDX: www.idx.co.id. Analysis of the data was use as Path Analysis, Correlation of Parcial test, R square, and the classical assumption test of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results that (1) the profitability is significant positive on the capital structure, (2) the leverage is significant positive on the capital structure, (3) the profitability is significant positive on the value of the company, (4) the leverage is significant positive on the value of the company, (5) the capital structure is significant positive on the value of the company, (6) the profitability is significant positive on the value of the company with capital structure as intervening variable, (7) the leverage is significant positive on the value of the company with capital structure as intervening variable.